2021
DOI: 10.1177/11772719211034685
|View full text |Cite
|
Sign up to set email alerts
|

suPAR Cut-Offs for Risk Stratification in Patients With Symptoms of COVID-19

Abstract: Objectives: Elevated soluble urokinase Plasminogen Activator Receptor (suPAR) is a biomarker associated with adverse outcomes. We aimed to investigate the associations between plasma suPAR levels (testing the cut-offs ⩽4, 4-6, and ⩾6 ng/mL) with risk of 14-day mortality, and with the risk of mechanical ventilation in patients that tested positive for SARS-CoV-2. Methods: Observational cohort study of patients presenting with symptoms of COVID-19 at Department of Emergency Medicine, Amager and Hvidovre Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 21 publications
4
27
0
Order By: Relevance
“…The length of hospital stay in this cohort of COVID-19 patients was mainly determined by the need for oxygen supplementation with gradual phasing out and not the need for rehabilitation, since rehabilitation primarily was carried out at another department. Our results are consistent with previous studies ( 16 , 47 ), but to our knowledge, suPAR has previously not been shown to independently reflect the cohesive length of hospital stay.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The length of hospital stay in this cohort of COVID-19 patients was mainly determined by the need for oxygen supplementation with gradual phasing out and not the need for rehabilitation, since rehabilitation primarily was carried out at another department. Our results are consistent with previous studies ( 16 , 47 ), but to our knowledge, suPAR has previously not been shown to independently reflect the cohesive length of hospital stay.…”
Section: Discussionsupporting
confidence: 93%
“…The length of hospital stay in this cohort of COVID-19 patients was mainly determined by the need for oxygen supplementation with gradual phasing out and not the need for rehabilitation, since rehabilitation primarily was carried out at another department. Our results are consistent with previous studies (16,47), but to our knowledge, suPAR has previously not been shown to independently reflect the cohesive length of hospital stay. Nevertheless, suPAR has previously been shown to correlate with a prolonged stay at hospital due to other serious conditions with excessive inflammation, such as cardiac surgery, pneumonia in children, and burn injuries (48)(49)(50).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… 10 suPAR seems extremely promising as a COVID‐19 prognostic marker and may assist in the early selection of patients who can be discharged and continue self‐isolation at home or must be admitted to the hospital and/or intensive care unit. 10 , 11 , 12 , 13 In order to investigate the prognostic ability of suPAR in COVID‐19, we designed the SPARCOL study to assess whether suPAR measured at hospital admission is associated with illness severity in adult patients hospitalized primarily for COVID‐19.…”
Section: Introductionmentioning
confidence: 99%